Domótica para asistir adultos mayores (2020)
Due to the increase in the number of seniors, where the age is over 65, and the existence of a high number of single-parent households, it is necessary to have elements that offer independence to this population group. Hence research was carried out where a system is proposed that allows monitoring, safety and comfort applications to seniors. Raspberry Pi was used as an embedded system to process data from different sensors, as well as interface for Internet of Things connectivity. The system's proposal focused on the automation of a home, listening to the entry and exit of authorized persons in the house, activating lights at the entrance of the house when detecting a person's entrance, temperature control of the enclosure and the feeling of the hummed ad; the data obtained when performing the described tasks was stored in the cloud in order to be reviewed online. The implemented system allows to regulate the conditions inside a house and maintain the right environment for the older adult, in the future it is expected to increase the number of parameters monitored and obtain a system that allows greater autonomy.